Graduate employability skills and career choices for business graduates from low-income families: a perspective from Universiti Malaysia Sabah - Ang, Magdalene Chooi Hwa (Universiti Malaysia Sabah, 2015)
The present study examined graduate employability skills from the perspective of the industry and that of soon-to-be graduates in a Malaysian public university to ascertain whether perception differential exists between the two groups. Additionally, it also investigated the career choices of the student sample. Data were accordingly obtained via 2 different sets of survey questionnaire prepared for the 2 target groups. The final sample was comprised of 34 employers and 251 graduates. The results confirm that there exists a variation and a broad understanding of what qualities, characteristics, skills and knowledge constitute employability both in general, and specifically for graduates. Another noteworthy finding is that the students seem to be in tune with their career development learning and are relatively confident about their academic performance jiving with their academic aspirations. And despite lacking work-relevant experience, they are also confident about promoting themselves to prospective employers. Perhaps, this confidence exudes from the perception that the University has prepped them well for the job market. Thirdly, the students' responses reveal their most favoured choice is a career In finance, followed by human resource management, accounting, and investment banking. Finally, gender gaps are found in terms of career choices and in how male and female students perceive employability skills and attributes. Data gleaned from the study can be usefully employed In the development of an "employability index" for graduates. Collectively, the study findings have Important implications for policy makers, employers, the government, and students with regards to enhancing employability rates among graduates from low-income families. The gender gaps found In the study also suggest that a gender-specific approach may be the way forward for universities in ensuring the effectiveness of employability programs.